TOOLKIT FOR BEHAVIORAL REGULATION IN PUBLIC GOVERNMENT BODIES - NINYUK, Inna; SEMYKRAS, Oleksandr; SULYM, Borys (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In today's world, public authorities play a critical role in the formation and implementation of policies that affect the social and economic activities of society. Ensuring effective behavioral regulation in these bodies becomes an extremely important task. The relevance of this study lies in the need to develop more complex and innovative tools for regulating the activities of public authorities. The research is aimed at studying the tools of behavioral regulation, which is used in public authorities in order to ensure greater compliance of their activities with the requirements of society and the achievement of strategic goals. The purpose of this study is to analyze and evaluate the tools of behavioral regulation in public authorities in order to identify effective approaches and opportunities for improving this process. The object of research is the toolkit of behavioral regulation in public authorities. The subject of research includes tools, methods and strategies that are used to influence the behavior of actors in the field of public administration. The study used a combination of several methods. First of all, an analysis of literary sources and publications on behavioral regulation in public authorities was carried out. Next, a quantitative analysis of the results of surveys of prominent government figures and high-ranking officials was conducted. Also, interviews and analysis of official documents were conducted to confirm and generalize the obtained data. Within the framework of this study, the main trends in the use of behavioral regulation tools in public authorities were determined, its advantages and disadvantages were identified, and recommendations for optimizing the regulation process were provided. The main conclusions of the study are the need for further research in this area for the development of more effective tools of behavioral regulation in public authorities. Understanding and applying these tools can help improve the quality of governance and ensure a greater level of accountability in the field of public administration.
Keywords: public administration; behavioral regulation; public authorities; regulatory tools of public authorities; nudges